Reduced Genetic Diversity in the Clown Anemonefish Amphiprion ocellaris in Exploited Reefs of Spermonde Archipelago, Indonesia - Madduppa, Hawis H.; Timm, Janne; Kochzius, Marc (Frontiers in Marine Science, 2018)
Populations of the clown anemonefish in Spermonde Archipelago, one of the main collection sites for ornamental fish in Indonesia, are potentially overfished, which might lead to a reduction in population size and genetic diversity. Loss of genetic diversity can reduce the adaptability, population persistence and productivity of the targeted species. Therefore, a study investigating the genetic diversity and its potential correlation to population densities of A. ocellaris was conducted. Two islands were chosen as study sites that differed in the degree of exploitation. Barrang Lompo has a high fishing pressure, whereas Samalona has less. Underwater visual censuses showed that population densities in Samalona were threefold higher than in Barrang Lompo (p = 0.005). Analysis of eight microsatellite loci in 364 tissue samples of A. ocellaris revealed that genetic diversity (numbers of alleles, private alleles, and allelic richness) was significantly reduced at the island with high fishing pressure. Allelic richness was also positively correlated with fish density (p < 0.05). These results indicate that ornamental fishery might be a factor contributing to the loss of genetic diversity in A. ocellaris. Therefore, the marine ornamental trade in Spermonde Archipelago needs to be managed (e.g. management of the fishing strategy, implementation of marine protected areas, regular monitoring and quota determination). Otherwise the populations of A. ocellaris might collapse.